Reimagining Ocean Stewardship: Arts-Based Methods to ‘Hear’ and ‘See’ Indigenous and Local Knowledge in Ocean Management - Strand, Mia; Rivers, Nina; Snow, Bernadette (Frontiers in Marine Science, 2022)
Current ocean management approaches are often characterised by economic or environmental objectives, paying limited consideration to social and cultural dimensions, as well as Indigenous and local knowledge. These approaches tend to inhibit ocean stewardship, often marginalising coastal communities or limiting people’s access to spiritual, traditional and recreational uses of the ocean and coast. Piloting arts-based participatory research methods to co-create knowledge with co-researchers in Algoa Bay, South Africa finds that these methods can be useful in highlighting cultural connections to the ocean, and remembering and imagining, or reimagining, ways in which people relate to and care for the ocean and coast. For example, using photography and in situ storytelling often allows people to convey memories and histories of more accessible coastlines, or envisaging a future with more inclusive and participatory ocean management. The study finds that there is a strong sense of exclusion from and lack of access to coastal and ocean areas in Algoa Bay where Indigenous and local communities have depended on for spiritual, cultural and recreational purposes for several generations. Co-creation of knowledge regarding connections, values and priorities of the coast and ocean with Indigenous and local communities should therefore be planned for before the implementation of integrated ocean management approaches and intentionally designed as part of adaptive management processes. Emphasising these cultural connections, and better recognising them in ocean management has the potential to include i people’s awareness of the ocean which could translate into an increased sense of care and stewardship towards the ocean and coast as people feel more connected to their contextual seascapes. This could in turn contribute to a more sustainable sociocultural approach to ocean management which is necessary for equitable and sustainable future ocean social-ecological wellbeing.